'Deal' or 'No Deal'? Impacts of Alternative Post‐Brexit Trade Agreements on UK Agriculture. (18th December 2017) - Feng, Siyi; Patton, Myles; Binfield, Julian; Davis, John
Summary: Brexit will have important implications for UK agricultural commodity markets due to potentially significant changes to trade flows. We quantify the sectoral impacts on UK agriculture of three illustrative scenarios, which capture a broad range of potential trade arrangements: Bespoke Free Trade Deal, WTO Default and Unilateral Trade Liberalisation . It is estimated that the projected market impacts are relatively small if the UK negotiates a Bespoke Free Trade Agreement with the EU. The projected impacts are much greater under the two other scenarios, which capture potential trade arrangements if 'no deal' is reached. The high tariffs imposed under the WTO default scenario lead to significant adjustments in trade between the UK and EU‐27, with the impact on the domestic UK market depending on whether the UK is a net importer or a net exporter of the relevant commodity. All sectors experience price and production declines under the trade liberalisation scenario in which the UK unilaterally sets tariffs on imports from both the EU‐27 and the rest of the world to zero; the impacts are particularly severe in the beef and sheep sectors where international competition is very strong. Abstract : Brexit will have important implications for UK agricultural commodity markets due to potentially significant changes to trade flows. We quantify the sectoral impacts on UK agriculture of three illustrative scenarios, which capture a broad range of potential trade arrangements: Bespoke Free Trade Deal, WTO Default and Unilateral Trade Liberalisation . It is estimated that the projected market impacts are relatively small if the UK negotiates a Bespoke Free Trade Agreement with the EU. The projected impacts are much greater under the two other scenarios, which capture potential trade arrangements if 'no deal' is reached. The high tariffs imposed under the WTO default scenario lead to significant adjustments in trade between the UK and EU‐27, with the impact on the domestic UK market depending on whether the UK is a net importer or a net exporter of the relevant commodity. All sectors experience price and production declines under the trade liberalisation scenario in which the UK unilaterally sets tariffs on imports from both the EU‐27 and the rest of the world to zero; the impacts are particularly severe in the beef and sheep sectors where international competition is very strong.